O Rio Grande do Sul como segundo polo industrial do país : uma análise da abertura empresarial gaúcha a uma nova ordem econômica 1971-1974 - Moraes, Gilmar Ferreira de (2012)
This study describes the situation of industrial development between 1970 and 1974, with the backdrop of the strategic action of the State and Federação da Indústria do Rio Grande do Sul (FIERGS) that aims to raise Rio Grande do Sul's industrial sector to a condition of the second industrial center of the country. Towards this direction, the overall objective of this study is to evaluate the degree of openness of the industrial entrepreneur from Rio Grande do Sul to a new economic order. Therefore, this study sought to ascertain the degree of openness achieved by the industry workers, through data related to levels of technological innovation, industrial policy, business mentality, business characteristics and from the politic action of the Federation and entrepreneur to the adoption of a new way of looking at the situation and to make choices in other bases. Thus through specific objectives, it was analyzed the state's political-institutional arrangement through the industrial policy, having as analysis object the program of financial incentives to encourage industrial investment, on the other hand, it was analyzed the Federation's strategic action with respect to the industrial policy and the matter of entrepreneurial qualification, as well as innovations for companies from Rio Grande do Sul. Thus the intent of these specific objectives is to accommodate a referential from which the indicated discussion will gain importance and intelligibility. In this context, came up as fundamental hypothesis that mechanisms created to be the second industrial center of the country, provided conditions for the formation of an entrepreneurial mentality to a new economic order that, at this juncture, it was stimulated by the need to face the problem of business excellence and competitive leadership with more intensity and effectiveness, even for the sake of their own survival.